Sifat - Sifat Fisik Mortar Geopolimer Dengan Bahan Dasar Campuran Abu Terbang (Fly Ash) Dan Abu Sawit (Palm Oil Fuel Ash) - Islami, Aldi Nauri; Olivia, Monita; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This research study about characteristic of physical of mortar geopolimer from blend of fly ash and palm oil fuel ash. Alkaline activator solution used to processed the activation of Silica (Si) and Alumina (Al) which implied in both types of the ash mixture from NaOH 14 M and liquid of natrium silicate (Na2SiO3). Proportion the blended fly ash and palm oil fuel ash ratios of 100:0, 25:75, 50:50, 75:25, and 0:100. Sand to blended ash by mass ratios of 2,75:1. Sampel out 5x5x5 cm on cube geopolymer. This research is used mix with the activator modulus 1,00 and 1,25, activator dosage (%Na2O) 22,5, cured at room temperature at 3 days and heat curedt 110ºC for 24 hours then cured at room temperature for 7 day. Result from this research represents compressive strength the mortar as according to variation blended ash. Compressive strength will mount as according to modulus of activator and activator dose with the correct combination blended ash.Keywords : geopolymer, fly ash, palm oil fuel ash, activator modulus, mix proportions